Properties of Biobased Rigid Polyurethane Foams Reinforced with Fillers: Microspheres and Nanoclay - Hongyu Fan; Ali Tekeei; Galen J. Suppes; Fu-Hung Hsieh (International Journal of Polymer Science)
The effect of incorporating 1–7% microsphere and nanoclay fillers on the physical properties of polyurethane (PU) foams containing 15% soybean oil-based polyol was investigated. Increasing filler percentage reduced the PU foam density. The compressive strength of PU foams decreased slightly when increasing the microsphere content from 1 to 3% and then increased. At 7% microsphere content, the foams displayed the same compressive strength as the control foams made from 100% petroleum polyol. For PU foams reinforced with nanoclay, their compressive strength changed little from 1 to 5%, but decreased at 7% due to a lower density and weaker matrix structure. Foams containing 5 to 7% microspheres or 3 to 7% nanoclay had density-compressive strength comparable or superior to the control. Foams reinforced with fillers had more cells and smaller cell size than foams made from 15% soy-polyol but without fillers. During the foaming process, the maximal temperatures reached by PU foams were not affected by the presence of 1 to 7% of microspheres or nanoclay, but slightly lower than the control. In addition, foams with fillers displayed roughly the same thermal conductivity as soy-polyol based foams without fillers.